PEMBELAJARAN MENULIS DI SEKOLAH DASAR - Yarmi, Gusti (Perspektif Ilmu Pendidikan, 2017)
The aims of this study is to find out the teacher’s understanding of the application of learning to writing in Islamic Primary School Jerapah Kecil, East Jakarta. Using ethnographic methods (Spradley model), this qualitative study was conducted in March-July 2013. The results of this study indicate that the teaching of writing in Islamic Primary School Jerapah Kecil has a unique in the learning objective. The students are expected to have writing skills through contextual writing practice and to enjoy writing. Through various writing activities the teacher builds positive attitude on the students. Beside the communicative and the whole language approaches, the teaching also implements student-centered approach. The students’ writing skills are developed through several kinds of writing activities at school and out of school. The students’ writing performance is asseesed not only based on their product but also writing process. Then assessment covers cognitive and affective aspects. Using a variety of learning resources in writing, such as museum, can develop the students’ positive attitudes.